Okay, here we have this:
Considering the provided information, we are going to replace in the function f(x)-g(x), with the given values of bounds:
Lower bound (x=4):
![\begin{gathered} f(4)-g(4)=2.5e^(-0.04\cdot\: 4)-0.2\cdot\: 4-1.2 \\ =2.5e^{\mleft\{-0.16\mright\}}-0.8-1.2 \\ =2.5\cdot(1)/(e^(0.16))-2 \\ \approx0.13 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/gq13zy04tlo4n1ykveawi2aroc7qts85gq.png)
The first value on the right side of the table is the one we just got.
Average of the bounds (x=4.5):
![\begin{gathered} f(4.5)-g(4.5)=2.5e^(-0.04\cdot\: 4.5)-0.2\cdot\: 4.5-1.2 \\ =2.5e^{\mleft\{-0.18\mright\}}-0.9-1.2 \\ =2.5\cdot(1)/(e^(0.18))-2.1 \\ =-0.01 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cbp6y6m0nggomlb3piik1wxam6e8jk77iv.png)
The second value on the right side of the table is the one we just got.
Upper bound:
![\begin{gathered} f(5)-g(5)=2.5e^(-0.04\cdot\: 5)-0.2\cdot\: 5-1.2 \\ =2.5e^{\mleft\{-0.2\mright\}}-1-1.2 \\ =2.5\cdot(1)/(e^(0.2))-2.2 \\ =-0.15 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dcznlpvvxt27wvrr2qhw9fnldcfu9aek5j.png)
The third value on the right side of the table is the one we just got.